Women, Global Reporting Initiative Standards (GRI), and Carbon Emission Disclosure: Are Women Eco-Friendly? Evidence from Banking in Indonesia - Anwar, Saiful; Rusanti, Ega; Maulidiyah, Dewi Rahmawati (Otoritas Jasa Keuangan, 2025)
This study aims to examine whether the adoption of the Global Reporting Initiative (GRI) Standards enhances carbon emission disclosure among banks in Indonesia. Furthermore, it provides empirical evidence that the presence of women on boards moderates the relationship between GRI adoption and carbon emission disclosure. The study was conducted on 40 conventional and Islamic banks listed on the Indonesia Stock Exchange (IDX) during the period 2015–2021. The analysis employs Ordinary Least Squares (OLS) regression, with robustness tests conducted using alternative measurement variables to ensure the consistency of the results. The findings consistently demonstrate that the adoption of GRI Standards positively influences carbon emission disclosure in Indonesian banks. The presence of women on boards promotes banks’ engagement in global climate change agendas, aligning with the implementation of Sustainable Development Goals (SDGs) 5, 8, and 13. This study reinforces stakeholder theory and Critical Mass Theory, indicating that a minimum threshold of female board members is necessary to influence strategic decisions, particularly in encouraging voluntary disclosures such as carbon emission reporting. Notably, the study also finds that carbon emission disclosure is valued by banking stakeholders in Indonesia. Therefore, policymakers are encouraged to establish regulations that mandate GRI adoption and ensure a minimum representation of women in strategic decision-making positions within the banking sector.